(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
This paper examines the fundamental elements required for operating a wind turbine (WT) at its maximum power point (MPP). It focuses on measuring the wind speed and the power output from the electric generator (EG) over time to establish the relationship between the optimal mechanical angular velocity (MAV) and the wind speed, denoted as the function ωOPTIM(V). This function is crucial for controlling the power output of the electric generator, ensuring that the WT operates at its maximum power point. The study analyzes the measurements taken from the turbines in Siliștea in Dobrogea, Romania. The paper concludes by presenting an algorithm to determine the function ωOPTIM(V).